Experiential Learning Assessment in Post-secondary Education - Jay Wilson; Tom Yates; Marc Gobeil; Alec Aitken; Kevin Lewis (Canadian Journal for the Scholarship of Teaching and Learning)
This article shares results from the research project “Experiential Learning Assessment in Post-Secondary Education.” The purpose of this research was to develop a further understanding of experiential learning assessment (EL) through an exploratory approach with university faculty and students. This article shares findings from the first part of a two-part research project examining the faculty experience of assessment in EL. A second research study is underway that provides the student perspective. The first phase of the research engaged University of Saskatchewan instructors with experience in experiential learning. Nine participants completed an online survey and six discussed their experiences and understanding in a focus group or an interview. Findings revealed that EL students were far more engaged with their learning than those in traditional courses. Participants applied their experience to expand upon current definitions and characteristics of EL assessment. They also shared differences with EL instruction and assessment as compared to traditional courses. Common themes identified by participants included a need for questioning and processes to integrate more EL assessment strategies into teaching and learning. Participants shared advice for those considering EL approaches in their own teachings. As EL continues to be a key area of growth for many universities and post-secondary institutions, this study contributes to the body of knowledge and appeals to faculty, designers, and others tasked with implementing effective EL.